Factors Affecting Audit Quality of BPKP – Central Java Chapter - Camelia Idriana Kurniadi; Samuel Martono; Gracella Theotama; Jean Stevany Matitaputty; David Adechandra Ashedica Pesudo (Perspektif Akuntansi, 2023)
This research aims to analyze the influence of machiavellianism, competency and motivation toward audit quality. This study uses a quantitative approach by using questionnaires that was distributed to 50 respondents to gather primary data. Respondents for this research are auditors at Badan Pengawasan Keuangan dan Pembangunan (BPKP) – Central Java Chapter. Research data was analyzed by using multiple linear regression analysis. The results show that (1) machiavellianism has negative effect on audit quality, (2) competence has positive effect on audit quality and (3) motivation has no effect on audit quality.